European Union Energy Producer Finance Emergency Regulation - Volkwein, Stephan (Teisė, 2025)
The inadequacy of the European Union energy policy became apparent during the natural gas crisis and nuclear energy crisis of 2021 to 2023. The Union also failed to recognize the signs of a looming oil crisis. This article describes the necessary correction of the Union law concerning the financing of renewable energies in the form of a new Regulation. To ensure that the Union is not surprised by another energy crisis, the Regulation must be adopted and implemented with due urgency. The instrument of the emergency Regulation is proposed here. The main content revolves around the partial replacement of the tendering and auction procedures with fixed feed-in tariffs for energy. The new emergency Regulation defines uniform feed-in tariffs for electrical, thermal, solid, liquid and gaseous energies throughout the EU. The European Commission can copy the complete text for the new emergency Regulation from this journal article and submit it to the Council for a decision.
Keywords: Energy emergency; financing; feed-in tariff; auctions; net metering